Transdisciplinarity in university education: Rhizomatic visions of transcomplex decolonial education - Rodriguez, Milagros Elena (Universidade Estadual de Campinas, 2021)
The present research has the complex objective of analyzing transdisciplinarity in University Education as rhizomatic visions of Trancomplex Decolonial Education; located in the line of research: education-trans-complex transepistemologies. It is carried out from deconstruction: a rhizomatic transmethod in transmodernity. In the reconstruction, after unveiling the crisis, arid points of the Venezuelan University Education; in a hopeful praxis that reveals Freirian love for decoloniality and liberation from the imposed disciplines, a quality of life of people as transdisciplinary educational challenges, onto-epistemological liberation of knowledge as utility, belonging and transcendence.